2015
DOI: 10.3892/or.2015.4518
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of rhein lysinate against human glioma U87 cells in vitro and in vivo

Abstract: In previous studies, we demonstrated that rhein lysinate (RHL), the salt of rhein and lysine that is easily dissolved in water, inhibited the growth of tumor cells derived from breast and ovarian cancer, hepatocellular carcinoma, cervical cancer and lung carcinoma. Based on these observations, human glioma U87 cells and a xenograft model in BALB/c nude mice were used to examine the antitumor activity of RHL against human glioma. Notably, RHL statistically significantly suppressed the growth of human glioma U87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…EGR1 exhibits a dual role of a tumor suppressor or a tumor-promoting factor in various carcinomas, by regulating cell cycle progression, apoptosis and malignant transformations (19)(20)(21). EGR1 stimulates cells proliferation in prostate, stomach, and kidney cancer (22)(23)(24), whereas it shows a tumor-suppressive activity in breast cancer, melanoma, fibrosarcoma and B cell lymphoma (25)(26)(27)(28). Our results also indicate a tumor-suppressive activity of EGR1 in CTCL.…”
Section: Discussionsupporting
confidence: 63%
“…EGR1 exhibits a dual role of a tumor suppressor or a tumor-promoting factor in various carcinomas, by regulating cell cycle progression, apoptosis and malignant transformations (19)(20)(21). EGR1 stimulates cells proliferation in prostate, stomach, and kidney cancer (22)(23)(24), whereas it shows a tumor-suppressive activity in breast cancer, melanoma, fibrosarcoma and B cell lymphoma (25)(26)(27)(28). Our results also indicate a tumor-suppressive activity of EGR1 in CTCL.…”
Section: Discussionsupporting
confidence: 63%
“…For instance, RHL was shown to reduce inflammation and adipose infiltration in KK/HlJ diabetic mice with non-alcoholic fatty liver disease (10). And RHL was suggested to suppress the progression of breast and ovarian cancer, hepatocellular carcinoma, cervical cancer and lung carcinoma mainly by downregulation of Bcl-2 and cyclin D expression and upregulation of BAX and Bim expression (18). In addition, RHL was demonstrated to protect the livers by reducing the expression of TNF-α and IL-6 and the phosphorylation of SREBP-1c and ERK1/2 in diabetic mice (19).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that RHL is characterized by anti‐inflammatory and antitumor features . In human glioma U87 cells, RHL is shown to induce cell apoptosis via suppressing Bcl‐2 and increasing Bax expression . In cervical cancer cells, RHL is found to suppress HeLa cell growth via p38 MAPK and JNK signaling pathway .…”
Section: Introductionmentioning
confidence: 99%
“…17,18 In human glioma U87 cells, RHL is shown to induce cell apoptosis via suppressing Bcl-2 and increasing Bax expression. 19 In cervical cancer cells, RHL is found to suppress HeLa cell growth via p38 MAPK and JNK signaling pathway. 20 However, whether RHL improves SCI and the underlying mechanism has not been reported.…”
Section: Introductionmentioning
confidence: 99%